Palliative care for the elderly in a long-stay institution in a municipality in west Pará: An experience report based on Arco de Maguerez - Gomes , Victor Alexandre Santos; Cajaíba , Ryan Ferreira; Costa , Juliane Nascimento; Damasceno , Pollyanna Ribeiro; Souza, Ana Julia de; Goto , Lucicleide Kubiczewski; Lima , Jéssica Priscila da Silva; Santos , Greice Nara Viana dos; Santos , Greice Nívea Viana dos; Figueira , Simone Aguiar da Silva (Seven Editora, 2023)
Human aging is a natural process that involves a variety of influences, including genetic, physiological, social, environmental, psychological and cultural factors. Therefore, this study addresses palliative care provided to elderly people residing in a long-term institution in a municipality in the west of Pará. The report seeks to understand and improve health care for the elderly population, especially in the context of chronic diseases and weaknesses physical or mental. Using the problematization methodology and the Maguerez Arc tool, the study aims to identify aspects related to palliative care offered to the elderly and develop an informative tool to improve the quality of care. Additionally, the research focuses on humanizing the care provided and helping ease death as a natural part of life for these elderly people, as well as providing useful information to nursing professionals and caregivers. DOI:https://doi.org/10.56238/interdiinovationscrese-059